2010
DOI: 10.1038/jes.2009.59
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposure to ultrafine particles

Abstract: Personal exposure to ultrafine particles (UFP) can occur while people are cooking, driving, smoking, operating small appliances such as hair dryers, or eating out in restaurants. These exposures can often be higher than outdoor concentrations. For 3 years, portable monitors were employed in homes, cars, and restaurants. More than 300 measurement periods in several homes were documented, along with 25 h of driving two cars, and 22 visits to restaurants. Cooking on gas or electric stoves and electric toaster ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
153
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(181 citation statements)
references
References 29 publications
9
153
1
2
Order By: Relevance
“…In their experiment with 22,973 1-sec readings from collocated monitors, they reported the coefficient of determination between the two monitors of R 2 ¼ 0.998. Wallace and Ott (2011) reported that the bulk of the particle size distribution of tobacco smoke by number count lies between 0.01 and 0.45 mm, which is within the 0.01-1.0 mm size range that the TSI-3007 measures (Hämeri et al, 2002;TSI, 2013b). Other investigators using the TSI-3007 condensation particle counter in and near traffic have referred to their measurements as "ultrafine particles" (Westerdahl et al, 2005;Jarjour et al, 2013;Quiros et al, 2013); although this instrument includes counts above the UFP range (>0.1 mm), we will use the term UFP in this paper to refer to these measurements.…”
Section: Instruments and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their experiment with 22,973 1-sec readings from collocated monitors, they reported the coefficient of determination between the two monitors of R 2 ¼ 0.998. Wallace and Ott (2011) reported that the bulk of the particle size distribution of tobacco smoke by number count lies between 0.01 and 0.45 mm, which is within the 0.01-1.0 mm size range that the TSI-3007 measures (Hämeri et al, 2002;TSI, 2013b). Other investigators using the TSI-3007 condensation particle counter in and near traffic have referred to their measurements as "ultrafine particles" (Westerdahl et al, 2005;Jarjour et al, 2013;Quiros et al, 2013); although this instrument includes counts above the UFP range (>0.1 mm), we will use the term UFP in this paper to refer to these measurements.…”
Section: Instruments and Measurementsmentioning
confidence: 99%
“…Wallace and Ott (2011) report a quality control comparison between two TSI-3007 monitors run side-by-side for 100 hr to determine their precision and relative bias. They found that the relative bias was 1-3%, and the mean of their relative precision, calculated as the sum of the absolute value of the differences divided by the sum of each measured pair, was 2.3%.…”
Section: Instruments and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…They estimated relative contribution to the typical 24 h daily nonsmoker style exposures by outdoor, indoor and in-vehicle sources as 36, 47 and 17%, respectively. This contribution was doubled for indoor (77%), nearly halved for outdoor (17%) and one-third for in-vehicle (6%) in the presence of a smoker smoking on an average 16 cigarettes per day in an averaged size house having volume of 400 m 3 and typical air exchange rates of about 0.75 h -1 [7]. As expected, the exposure contribution from outdoor sources can decrease in rural areas and increase in urban areas due to a greater mobility of road vehicles.…”
mentioning
confidence: 99%
“…After the switching off indoor sources, concentration decay generally occurs at a much slower rate due to the surrounding built up environment restricting the ventilation and dilution. A recent study, based on suburban areas in USA, characterised the indoor sources in detail [7]. They estimated relative contribution to the typical 24 h daily nonsmoker style exposures by outdoor, indoor and in-vehicle sources as 36, 47 and 17%, respectively.…”
mentioning
confidence: 99%